Drink combination made from Fenugreek seeds and Phoenix dac-tylifera to increase prolactin hormone levels in postpartum mothers and its impact on baby weight - Siti Halimah; Krisdiana Wijayanti; Taadi Taadi (Medisains, 2022)
Background: Breast milk is the best leading food for the growth and development of the baby; however, the production of breast milk produced by breastfeeding mothers is still lacking and impacts the baby's weight. One of the efforts is consuming a combination drink of Fenugreek seeds and Phoenix dactylifera containing galactagogue, which has never been done in this study before, to see an increase in breast milk production from indicators of prolactin hormone levels and its impact on baby weight.